High-pressure carbon dioxide/water pre-treatment of sugarcane bagasse and elephant grass: Assessment of the effect of biomass composition on process efficiency. (January 2017) - Toscan, Andréia; Morais, Ana Rita C.; Paixão, Susana M.; Alves, Luís; Andreaus, Jürgen; Camassola, Marli; Dillon, Aldo José Pinheiro; Lukasik, Rafal M.
Highlights: High-pressure CO2 /H2 O proved to be an efficient pre-treatment technology. Biomass composition is the most important factor on pre-treatment efficiency. The conditions for maximal C5 -sugar recovery yield were different for each biomass. Maximal saccharification yield for both biomasses was obtained at similar conditions. CO2 /H2 O mixture showed to be a greener alternative to conventional pre-treatments. Abstract: The performance of two lignocellulosic biomasses was studied in high-pressure carbon dioxide/water pre-treatment. Sugarcane bagasse and elephant grass were used to produce C5 -sugars from hemicellulose and, simultaneously, to promote cellulose digestibility for enzymatic saccharification. Different pre-treatment conditions, with combined severity factor ranging from −1.17 to −0.04, were evaluated and maximal total xylan to xylose yields of 59.2 wt.% (34.4 wt.% xylooligomers) and 46.4 wt.% (34.9 wt.% xylooligomers) were attained for sugarcane bagasse and elephant grass, respectively. Furthermore, pre-treated biomasses were highly digestible, with glucan to glucose yields of 77.2 mol% and 72.4 mol% for sugarcane bagasse and elephant grass, respectively. High-pressure carbon dioxide/water pre-treatment provides high total C5 -sugars and glucose recovery from both lignocellulosic biomasses; however it is highly influenced by composition and intrinsic features of each biomass. The obtained results confirm this approach as an effective and greener alternative to conventional pre-treatment processes.